Impact of Human Resource Information System on HR Manager’s Professional Standing - Kapoor, T; Chhabra, I (International Journal of Computer Sciences and Engineering, 2025)
Today companies begin to compete in the challenging business environment of the new millennium, an everincreasing reason for success lies in the function of effective Human Resource Management (HRM). In the Last few years Human Resource function has changed within organization. Its function has grown considerably and has shifted into a more strategic role rather than providing support for administrative paperwork. Today organization deploys the information system for achieving efficiency, effectiveness, enhancing quality and gaining competitive advantage. To achieve same objective Human Resource department deploy Human Resource Information System (HRIS). Human Resource Information System is an intersection of human resource management and information technology. Human Resources Information Systems is now expected to drive Human Resource (HR)'s transition from an administrative and operational role to a strategic role. Despite the growing presence of Information Technology within organizations, however we do not have clear understanding of how Information Technology impacts the role of Human Resource Professional. This paper analyzes impact of Human Resource Information System on Human Resource’s Professional standing. It attempts to examine how HR manager’s in different organizations see the effects of Human Resource Information System on strategic Human Resources tasks and job roles. Also tries to find out if there is any significant difference in the usage of Human Resource Information System between small/medium (SME) size and large size companies. The questionnaire was sent to 300 companies out of which 114 were received and complete. Response rates were 38.333